Cooperation, Mutual Respect, and Societal Commitment: Meanings of Gotong-Royong in Indonesian Social Studies School-textbooks - Aryaningsih, Mila; Wardana, Amika; Sheikh, Karim Sajjad (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2024)
The study aims to explore the meanings of gotong-royong, a core national and cultural value in Indonesia, as it is presented and disseminated in the Social Studies curriculum, particularly at the lower secondary level. Since introducing character education in 2017, the Ministry of Education and Culture has sought to promote the value of gotong-royong among students to foster and maintain a peaceful and harmonious society. This research involved a quantitative and qualitative content analysis of 11 Social Studies textbooks published and used in Indonesian schools over the past decade. The analysis examined the forms and meanings of gotong-royong presented to students in various social and cultural contexts. The findings revealed three general meanings associated with gotong-royong: (i) cooperation and social support (56%), (ii) mutual respect for all members of society (33%); and (iii) societal commitment (8%). Although the meanings of gotong-royong are not equally represented, the study found that this value has been readily adopted and integrated into the local and national civic and social values presented in the Social Studies textbooks for lower secondary education.